Universal Electrochemical Synthesis of Mesoporous Chalcogenide Semiconductors: Mesoporous CdSe and CdTe Thin Films for Optoelectronic Applications. Issue 17 (17th March 2021) - Nagaura, Tomota; Phan, Hoang‐Phuong; Malgras, Victor; Pham, Tuan‐Anh; Lim, Hyunsoo; Ashok, Aditya; Kim, Jeonghun; You, Jungmok; Nguyen, Nam‐Trung; Na, Jongbeom; Yamauchi, Yusuke
Abstract: Here we report the soft‐template‐assisted electrochemical deposition of mesoporous semiconductors (CdSe and CdTe). The resulting mesoporous films are stoichiometrically equivalent and contain mesopores homogeneously distributed over the entire surface. To demonstrate the versatility of the method, two block copolymers with different molecular weights are used, yielding films with pores of either 9 or 18 nm diameter. As a proof of concept, the mesoporous CdSe film‐based photodetectors show a high sensitivity of 204 mW −1  cm 2 at 680 nm wavelength, which is at least two orders of magnitude more sensitive than the bulk counterpart. This work presents a new synthesis route for nanostructured semiconductors with optical band gaps active in the visible spectrum. Abstract : This work demonstrates a novel route for the synthesis of mesoporous semiconductor films. The pore size can be controlled through the molecular weight of the block copolymers, and the synthesized mesoporous CdSe film exhibits a high sensitivity of 204 mW −1  cm 2 at 680 nm as a photodetector. This facile synthesis method shows a high potential for new optoelectronic applications.